A Technical Review of MPPT Algorithms for Solar Photovoltaic System: SWOT Analysis of MPPT Algorithms - Muhammad Mateen Afzal Awan (Sir Syed University Research Journal of Engineering and Technology)
To continuously operate the Photovoltaic (PV) system at its Maximum Power Point (MPP) under changing weather is a challenging task. To accomplish this, multiple MPP Tracking (MPPT) algorithms have been proposed, which can be portioned into two: 1) Conventional algorithms, have the strengths of a simple structure, fewer computations, and low memory requirement, and cheap implementation. Whereas, trapping under Partial Shading Conditions (PSC), steady-state oscillations, and system dependency are the associated drawbacks. Conversely, 2) Soft computing algorithms, perform efficiently under all weather conditions with zero steady-state oscillations, and are system independent. The structural complexities, giant computations, huge memory requirements, and expensive implementation, are the accompanying concerns. The core contribution of this study is to present a deep analysis of all the MPPT algorithms at the standard benchmarks defined in the published literature, for the readers so they could decide which algorithm to choose under certain circumstances.